Biomedical Advances in Nursing Practice: A Review of Emerging Technologies and Their Impact on Patient Care (Journal of Advances and Scholarly Researches in Allied Education, 2026)
Nursing practice is evolving with the integration of biomedical technologies. This review explores emerging technologies like wearable devices, telehealth, and electronic health records (EHRs) in nursing practice. We discuss their impact on patient care, benefits, and challenges. By understanding these advances, nurses can enhance care delivery and patient outcomes.